Revision of the genus Syzeuctus Förster, 1869 (Hymenoptera, Ichneumonidae, Banchinae) from Japan - Watanabe, Kyohei; Riedel, Matthias (Zootaxa, 2024)
Japanese species of the genus Syzeuctus Förster, 1869 are revised, with a total of 12 species recorded from Japan. Five species, S. brevicaudus sp. nov., S. flavitarsis sp. nov., S. nigrus sp. nov., S. rufiapicalis sp. nov., and S. yamatonis sp. nov., are newly described. Three species, S. flavofacialis Kang & Lee, 2020, S. laoticus Riedel, 2022, and S. maculatus Sheng, 2009, are newly recorded from Japan. Male of S. maculatus is newly described. A key for Japanese species is also provided.